A finite-difference time-domain FDTD) software for simulation of printed circuit board (PCB) assembly - Kung, Fabian Wai Lee; Chuah, Hean Teik (PIER, 2005)
This paper describes the design of a three-dimensional (3D) finite-difference time-domain (FDTD) simulation software for printed circuit board (PCB) modeling. The flow, the dynamics and important algorithms of the FDTD simulation engine will be shown. The software is developed using object-oriented programming (OOP) approach, to enable code reuse and ease of upgrade in future. The paper begins by looking at how a 3D PCB structure is created using cubes, and proceed to show the inclusion of various lumped components such as resistors, capacitor, inductor and active semiconductor components into the model. The architecture of the FDTD simulation program is then carefully explained. Finally a few sample simulation examples using the software will be illustrated at the end of the paper.